2020
DOI: 10.1177/0962280220938088
|View full text |Cite
|
Sign up to set email alerts
|

Using gradient boosting with stability selection on health insurance claims data to identify disease trajectories in chronic obstructive pulmonary disease

Abstract: Objective We propose a data-driven method to detect temporal patterns of disease progression in high-dimensional claims data based on gradient boosting with stability selection. Materials and methods We identified patients with chronic obstructive pulmonary disease in a German health insurance claims database with 6.5 million individuals and divided them into a group of patients with the highest disease se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Researchers may be interested in moving beyond descriptive research when investigating trajectories of social and health outcomes and instead adopt a predictive lens if different states or trajectories are already defined by the topic, for example, disease severity or educational or occupational level. A study investigated predictors of chronic obstructive pulmonary disease of highest severity and common disease trajectories with gradient boosting and a shifting time window approach in health claims data: The authors identified a number of diagnoses (e.g., respiratory failure), medications (e.g., anticholinergic drugs), and procedures associated with a subsequent chronic obstructive pulmonary disease diagnosis of highest severity ( 91 ). The temporal patterns detected in this study rather represent order of health care–relevant diseases and should not be interpreted in the sense of causal pathways ( 91 ).…”
Section: For Predictionmentioning
confidence: 99%
See 1 more Smart Citation
“…Researchers may be interested in moving beyond descriptive research when investigating trajectories of social and health outcomes and instead adopt a predictive lens if different states or trajectories are already defined by the topic, for example, disease severity or educational or occupational level. A study investigated predictors of chronic obstructive pulmonary disease of highest severity and common disease trajectories with gradient boosting and a shifting time window approach in health claims data: The authors identified a number of diagnoses (e.g., respiratory failure), medications (e.g., anticholinergic drugs), and procedures associated with a subsequent chronic obstructive pulmonary disease diagnosis of highest severity ( 91 ). The temporal patterns detected in this study rather represent order of health care–relevant diseases and should not be interpreted in the sense of causal pathways ( 91 ).…”
Section: For Predictionmentioning
confidence: 99%
“…A study investigated predictors of chronic obstructive pulmonary disease of highest severity and common disease trajectories with gradient boosting and a shifting time window approach in health claims data: The authors identified a number of diagnoses (e.g., respiratory failure), medications (e.g., anticholinergic drugs), and procedures associated with a subsequent chronic obstructive pulmonary disease diagnosis of highest severity ( 91 ). The temporal patterns detected in this study rather represent order of health care–relevant diseases and should not be interpreted in the sense of causal pathways ( 91 ). In other contexts, detected temporal patterns may be more robust.…”
Section: For Predictionmentioning
confidence: 99%
“…From the learned parameters, a graph of disease-symptom connections was elicited, and the developed knowledge graphs were assessed and approved, with consent, against Google's Temporal patterns in patient disease trajectories are either disregarded or only taken into account by assessing the temporal directionality of identified co-morbidity pairs [14], [15], [16], Which concludes naturally patients undergo different symptoms at different time instances on disease trajectories (stages of the disease). In this experiment, the temporal pattern for each disease as the preliminary basis of a disease prediction model is utilized.…”
Section: A Data Collection and Preparationmentioning
confidence: 99%
“…For example, claims data are used to optimize health service provisions, 1 estimate the prevalence and incidence of diseases, 2 or identify patients at risk of hospital readmission. 3 While claims data have been extensively used for disease prediction, [4][5][6] much less attention has been paid to their vast amount of (implicit) information on disease dynamics over time, such as (changes in) medication, hospital stays, or the frequency of physician consultations (but see Ploner et al 7 ). In this contribution, we thus draw on these comprehensive datasets to model the temporal courses of diseases and to learn about patients' health conditions over time.…”
Section: Introductionmentioning
confidence: 99%